Effects of Replacing Soybean Meal with Fermented Leaves and Seeds of the Rubber Tree (Hevea brasiliensis) on the Production Performance and Carcass Cholesterol Levels of Pitalah Ducks - Syahruddin , Erman; Herawaty, R.; Azhar (International Journal of Poultry Science, 2017)
Objective: This study aimed to determine the production performance and cholesterol content of Pitalah ducks fed a diet in which soybean meal had been replaced with rubber tree leaves and seeds fermented with the fungus Trichoderma spiralis. Methodology: A 12 week field trial was performed using 480, 1 day old Pitalah ducklings that were maintained in colonies in wire cages. Each unit was equipped with a feed enclosure, water and an incandescent light source. This randomized study was performed with 6 treatments, 4 replicates and 20 ducklings per box. The data were analyzed by ANOVA and differences among treatment groups were analyzed with Duncan’s multiple range test. The treatments included a control diet and diets in which a percentage of the soybean meal (20, 40, 60, 80 and 100%) was replaced with fermented leaves and seeds of the rubber tree (FLSRT). The variables measured were feed consumption, body weight gain, feed conversion, carcass percentage, income over feed cost and carcass cholesterol content. Results: Broiler production factors, such as feed intake, body weight gain, feed conversion, carcass percentage, income over feed cost and carcass cholesterol content, were not markedly affected by the inclusion of up to 80% FLSRT in livestock rations. Conclusion: Up to 80% of the soybean meal in Pitalah duck rations can be replaced with FLSRT.